Promoting Scientific Literacy in Chemistry Learning on the Subject Colloid through Instructional Material Development - Hatta; Miterianifa; Octarya, Zona (Journal of physics. Conference series, 2021)
Students’ scientific literacy skills are still low because they are still minimal or not the availability of chemistry teaching materials that contain balanced scientific literacy skills. The research objective was to develop scientific literacy-based chemistry teaching materials that contain balanced scientific literacy, validity, readability, and effectiveness. This research conducted research and development methods with the ADDIE approach which consists of five steps; analyze, design, develop, implement, and evaluation. Based on the research results, the teaching materials were based on science literacy colloid material which developed has the characteristics of a balanced scientific literacy content, namely 41,17% of science as the body of knowledge, 17,64% of science as a way of investigating, 17,64% science as a way of thinking, and 23,52% interaction of science, technology, and society. 7 validators of scientific literacy-oriented teaching materials were declared feasible and have criteria easy to understand with average readability of 74.11%. An increase in scientific literacy skills students who use science literacy-based teaching materials is higher than students who using teaching materials used in school.